Efektifitas Konseling Eklektif dengan Perilaku Attending untuk Mengurangi Masalah Belajar Siswa Kelas IX di SMP Bilingual Terpadu Krian Sidoarjo - Trisno, Trisno (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2020)
This research is a research type of Counseling Guidance Action. This research raises about eclective counseling by attending and students learning problems. The purpose of this study was to determine the effectiveness of eclectic counseling with attending behavior to reduce learning problems for class IX students of SMP Bilingual Terpadu Krian Sidoarjo. The research method used in analyzing the data in this study is qualitative. The research process took place in two cycles, namely cycle I and cycle II. Cycle I is the stage where the treatment is first carried out after conducting an assessment and preparation of an action plan. Cycle II is a follow-up action taken after cycle I is deemed less than optimal, therefore the researcher designed and implemented cycle II. The research subjects were students of class IX in the 2020/2021 academic year who after initial observations were taken 3 people who have a level of learning problems that are considered the highest of other students. Data collection techniques used interviews and observation through group counseling. In this research it was found that there were significant changes in the problems the students faced tended to improve. With the results of the first cycle of 46 (low) and the results of the second cycle of 68.33 (moderate). Based on this research, it can be concluded that the effectiveness of exclusive counseling with attending behavior to reduce the learning problems of class IX students of SMP Bilingual Terpadu.